Disparities in diabetes prevalence and preventable hospitalizations in people with intellectual and developmental disability: a population‐based study. Issue 2 (7th October 2014) - Balogh, R. S.; Lake, J. K.; Lin, E.; Wilton, A.; Lunsky, Y.
Abstract Aims To describe and compare population‐level aspects of diabetes and diabetes primary care among people with and without intellectual and developmental disabilities. Methods Administrative health data accessed from the Institute for Clinical Evaluative Sciences was used to identify a cohort of Ontarians with and without intellectual and developmental disabilities between the ages of 30 and 69 years (n = 28 567). These people were compared with a random sample of people without intellectual and developmental disabilities (n = 2 261 919) according to diabetes prevalence, incidence, age, sex, rurality, neighbourhood income and morbidity. To measure diabetes primary care, we also studied hospitalizations for diabetes‐related ambulatory care‐sensitive conditions. Results Adults with intellectual and developmental disabilities had a consistently higher prevalence and incidence of diabetes than those without intellectual and developmental disabilities. Disparities in prevalence between those with and without intellectual and developmental disabilities were most notable among women, younger adults and those residing in rural or high income neighbourhoods. In terms of hospitalizations for diabetes‐related ambulatory care‐sensitive conditions, people with intellectual and developmental disabilities were 2.6 times more likely to be hospitalized. Conclusions Adults with intellectual and developmental disabilities are at high risk of developing and being hospitalized for diabetes. The findings of the present study have a number of important implications related to the early detection, prevention and proper management of diabetes among adults with intellectual and developmental disabilities.